TU8.12 Group and Screen for Laparoscopic Appendicectomies: Is It Necessary?. (9th August 2022) - Bradley, Rebecca; Linder, Cortland; Marsden, Max; Abraham, Adjit
Abstract: Background: Blood transfusion is rarely required in laparoscopic appendicectomies. The incidence of major vessel injury is 0.04%, yet many trusts require two valid G+S samples prior to the operation. A retrospective review was conducted to assess the incidence of peri-operative blood transfusion in laparoscopic appendicectomies in a large tertiary centre, to challenge the requirement for these G+S samples in the hope to reduce clinical and financial burden. Methods: A retrospective case note review of patients undergoing emergency laparoscopic appendicectomies in the Royal London Hospital was conducted from 01/06/21 – 01/12/21. Patients under 18 years and those who received an appendicectomy as a concurrent procedure during other operations were excluded. The monetary value of each G+S sample was investigated through discussion with laboratory staff, and a total saving was calculated. Results: 95 patients were included. 93 patients had two valid G+S samples prior to their appendicectomy. No patients required perioperative blood transfusion (within two days pre and post op). One patient required a blood transfusion in the 5 th postoperative day. An estimated total of £10, 500 could be saved per year in this hospital alone, should G+S samples not be required for laparoscopic appendicectomies based on this data. Conclusions: We concluded that two G+S samples are not necessary for every patient undergoing a laparoscopic appendicectomy. The incidence of transfusion is scarce throughout literature, and it appears that the financial and clinical burden of these blood samples far outweighs the population transfusion requirement in this particular surgery